A Structural and Enzymatic Characterization of Purified Human Diacylglycerol Kinase Epsilon - Jennings, William (My University, 2016)
Diacylglycerol kinases (DGK’s) tightly regulate the intracellular levels of diacylglycerol (DAG) and phosphatidic acid (PA). DAG is an important intermediate in lipid biosynthetic pathways and acts as a lipid second messenger in a number of signaling pathways. Similarly, since PA serves as a potent signaling lipid and is a precursor for lipid biosynthesis, intracellular PA levels must be tightly regulated. There are ten isoforms of DGK in mammals, but we have decided to focus solely on the epsilon form (DGKε) in this work. DGKε is the only isoform that shows specificity for the acyl chains of its DAG substrate; as a consequence, it contributes to the dramatic enrichment of cellular lipids with sn-1 stearoyl and sn-2 arachidonoyl. The most notable example is the highly enriched bioactive lipid 1-stearoyl-2-arachidonoyl phosphatidylinositol. We have purified active human DGKε to near homogeneity and thoroughly characterized its stability as well as examined its secondary structure with CD. We also purified a truncated form (DGKε Δ40) that shows increased stability compared to the full-length protein. Our purified fractions are well suited for a wide range of exciting applications and studies. We have begun incorporating DGKε into liposomes in order to develop a liposome-based assay, which would be a dramatic improvement over the presently used micelle-based assay. This purification also allows for high throughput screens of chemical compounds to test for a specific inhibitor. These studies will reveal valuable information about the structural and functional properties of DGKε and will aid in the development of therapies for DGKε-related diseases.
﻿Purification and Characterization of Diacylglycerol Kinase Epsilon
Keywords: Membrane Protein Biochemistry